Semi-solid sodium ion battery and sodium ion battery additive

By using sulfide additives synthesized by doped metal organic framework compounds in sodium ion batteries and subjecting high-temperature sulfur permeability to form carbonized MOFs, the shortcomings of sulfide solid electrolytes in thermal stability and chemical stability are solved, and the safety performance and cycling stability of semi-solid sodium ion batteries are improved.

CN119650819APending Publication Date: 2025-03-18XIANGTAN ELECTROCHEMICAL SCI CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411753437.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Sulfide solid electrolytes have shortcomings in thermal stability and chemical stability, which affect the safety performance and cycling stability of the battery.

Method used

The doped metal organic frame compound is used as the sodium ion battery additive to synthesize sulfides under a reducing atmosphere, and carbonized MOFs with high porosity and conductivity are formed by high-temperature sulfur permeability treatment.

Benefits of technology

The thermal stability, oxidation resistance and corrosion resistance of semi-solid sodium ion batteries are improved, allowing the battery to have higher safety performance and cycle stability over a wider temperature range and in a harsh chemical environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650819A_ABST
    Figure CN119650819A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-solid sodium-ion battery and a sodium-ion battery additive, and belongs to the technical field of energy materials, the general formula of the semi-solid sodium-ion battery is Na < x > (TM) O < 2 >, TM is one or a combination of transition metal ions, and x is more than or equal to 0.44 and less than or equal to 1.0; the semi-solid sodium-ion battery contains a sodium-ion battery additive, and the sodium-ion battery additive is a sulfide synthesized from a doped metal organic framework compound in a reducing atmosphere. The semi-solid sodium ion battery is prepared by adopting a method of combining sulfide and a small amount of liquid electrolyte, the sulfide is made of a loose and porous material, and holes are filled with the liquid electrolyte, so that the specific surface area and sodium ion transmission channels are increased, and the ionic conductivity is further increased. A reinforcing framework is introduced into the electrode plate, so that the mechanical strength of the electrode plate is improved, and the safety performance of the semi-solid sodium-ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of energy materials, and in particular relates to a semi-solid sodium ion battery and a preparation method thereof, and a sodium ion battery additive. Background Art

[0002] At present, solid electrolytes are non-flammable, high temperature resistant, non-corrosive, non-volatile, and have better mechanical strength, thermal stability and electrochemical stability than traditional electrolytes, which fundamentally improves the safety level of batteries. The contact between traditional liquid electrolytes and positive and negative electrodes is liquid-solid contact, with good interface wettability and no large resistance between interfaces. However, solid electrolytes and positive and negative electrodes are in solid-solid interface contact, with a small contact area and poor tightness. The ionic conductivity is usually two orders of magnitude lower than that of liquid electrolytes. This characteristic leads to limited fast charging performance of batteries. Since the solid-solid interface is a rigid contact, it is more sensitive to the volume change of the electrode material. Stress accumulation during charging and discharging will also cause electrochemical performance to decay, affecting the cycle stability of the battery. In addition, the thermal stability and chemical stability are relatively poor: sensitive to air and water, easy to decompose and release toxic gases. Although sulfide solid electrolytes have advantages in high ionic conductivity and good interface contact, they are deficient in thermal stability and chemical stability, which need to be further improved. Summary of the invention

[0003] The present application provides a semi-solid sodium ion battery and a sodium ion battery additive, which aims to solve the problem of insufficient thermal stability and chemical stability of sulfide solid electrolytes to a certain extent.

[0004] In a first aspect, the present application provides a semi-solid sodium ion battery, the general formula of the semi-solid sodium ion battery is: Na x (TM)O2, wherein TM is one or a combination of several transition metal ions, 0.44≤x≤1.0; the semi-solid sodium ion battery contains a sodium ion battery additive, and the sodium ion battery additive is a sulfide synthesized by a doped metal organic framework compound under a reducing atmosphere.

[0005] In one embodiment, the preparation method comprises the following steps:

[0006] S1, taking positive electrode slurry and sodium ion battery additives, ball-milling and mixing, and then evenly coating them on aluminum foil, and obtaining positive electrode sheets after drying;

[0007] S2, adding electrolyte to the positive electrode sheet obtained in S1 as a positive electrode to assemble the semi-solid sodium ion battery.

[0008] In one of the embodiments, S1 the positive electrode slurry includes a positive electrode active material, a conductive agent, a binder and a solvent; the positive electrode active material is at least one of layered transition metal oxides and modified compounds thereof, tunnel-type oxides and modified compounds thereof, etc., the binder is at least one of vinylidene fluoride, polytetrafluoroethylene, and fluorine-containing acrylic resin, the conductive agent includes at least one of carbon black, carbon nanotubes, acetylene black, graphene and carbon nanofibers, and the solvent is N-methylpyrrolidone.

[0009] In one embodiment, the amount of the sodium ion battery additive added is 0.01 wt% to 0.1 wt% of the mass of the positive electrode active material.

[0010] In one of the embodiments, the added mass ratio of the positive electrode active material, the conductive agent, the binder and the solvent is: (6-10): (1-10): (1-10): (10-30).

[0011] In one of the embodiments, the amount of the electrolyte added in S2 is 1 wt % to 10 wt % of the mass of the positive electrode active material.

[0012] In one embodiment, the electrolyte in S2 is an ester solvent, and the ester solvent includes one or more combinations of ethylene carbonate, propylene carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, methyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl butyrate, ethyl propionate and ethyl butyrate.

[0013] The preparation method provided by the present invention is simple, has high production efficiency, and uses abundant raw material resources, is environmentally friendly, and is inexpensive. Compared with the prior art, the present invention adopts a method of combining sulfide with a small amount of liquid electrolyte to prepare a semi-solid sodium ion battery, wherein the sulfide is composed of a loose and porous material and the pores are filled with liquid electrolyte, which increases the specific surface area and the channel for sodium ion transmission, and further increases the ion conductivity. The reinforcing skeleton is introduced into the electrode sheet, which improves the mechanical strength of the electrode sheet and further improves the safety performance of the semi-solid sodium ion battery.

[0014] In the second aspect, the present application provides a sodium ion battery additive for the semi-solid sodium ion battery described in the first aspect, which is a metal organic framework compound obtained by carbonization infiltration, and the carbonization infiltration process is synthesized by low-temperature sintering of the doped metal organic framework compound and sulfur powder in a reducing atmosphere; the sodium ion battery additive is a combination of one or more of cobalt sulfide, molybdenum sulfide, zinc sulfide, selenium sulfide, nickel sulfide, manganese sulfide, tin sulfide, and copper sulfide.

[0015] In one embodiment, the doped metal organic framework compound is a porous material assembled by metal ions or metal clusters and organic ligands through coordination bonds or other interaction forces, the metal ions are a combination of one or more transition metals, rare earth metals or alkaline earth metals, and the organic ligands are nitrogen-containing or oxygen-containing compounds, including a combination of one or more carboxylic acid compounds, pyridine compounds, and imidazole compounds.

[0016] Doped metal organic framework compounds are porous materials assembled by metal ions or metal clusters (nodes) and organic ligands (linkers) through coordination bonds or other interaction forces. There is no unified general formula for this metal organic framework compound, because their composition and structure can vary greatly depending on the metal ions, organic ligands and synthesis conditions. These components are connected to each other through coordination bonds, hydrogen bonds, π-π stacking and other interaction forces to form MOF materials with different network structures.

[0017] In one embodiment, during the carbonization and sulfurization process, the ratio of the carbonized doped metal organic framework compound to the sulfur powder is 1:1-5, and the temperature of the low temperature sintering is 500°C-700°C. The actual process of "carbonization and sulfurization" is: the metal organic framework compound is sintered into porous carbon in a reducing atmosphere, and the sulfur powder melts and penetrates into the porous carbon pores during the sintering process.

[0018] The specific production method of the semi-solid sodium-ion battery is as follows: the above-mentioned sodium-ion battery positive electrode material plate with the new additive is punched into a disc using a cutting machine, a fixed mass of electrolyte is added, and a glass fiber separator (Whatman GF AF), a gasket, a negative electrode is a sodium sheet or hard carbon, and a sealing machine is used to complete the assembly.

[0019] In this embodiment, the positive electrode current collector and positive electrode active material, negative electrode current collector and negative electrode active material, electrolyte, separator, gasket, etc. of the sodium ion battery are all conventional technical means in the art.

[0020] Compared with the prior art, this solution introduces an innovative new additive. This additive converts the organic ligands in MOFs into carbonaceous materials at high temperatures through high-temperature sulfurization treatment, while retaining the skeleton structure of metal ions or clusters. This structure gives the carbonized MOFs high porosity, good conductivity, mechanical stability and chemical stability. Therefore, the semi-solid-state battery emphasized in this patent has better thermal stability, oxidation resistance and corrosion resistance than the same type of sulfide semi-solid electrolytes, so that the invented semi-solid-state battery can be used in a wider temperature range and harsher chemical environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 This is an X-ray powder diffraction spectrum of the new additive material for sodium ion batteries prepared in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the new additive material for sodium ion batteries prepared in Example 1 of the present invention;

[0024] Figure 3 This is a mapping diagram of the new additive material for sodium ion batteries prepared in Example 1 of the present invention;

[0025] Figure 4 is the XPS graph of the pole piece prepared in Example 1 of the present invention,

[0026] Figure 5 is the charge and discharge curve of the semi-solid sodium ion battery prepared in Example 1 of the present invention;

[0027] Figure 6 1 is a cycle performance test diagram of Example 1 of the present invention and Comparative Example 1;

[0028] Figure 7 It is a rate performance test diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0031] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0034] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0035] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0038] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.

[0039] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.

[0040] Embodiment 1:

[0041] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0042] (1) The specific preparation method of the positive electrode sheet is:

[0043] NeNi 0.33 Fe 0.33 Mn 0.33 O2, conductive agent acetylene black, and binder PVDF are dissolved in NMP in a mass ratio of 90:5:5, and stirred evenly to obtain an initial positive electrode slurry;

[0044] (2) The specific preparation method of the cobalt sulfide additive is as follows: dissolve cobalt sulfate and dimethylimidazole in methanol respectively, then pour the dimethylimidazole solution into the cobalt sulfate solution, stir for 2 hours, let stand for 6 hours, centrifuge and wash with methanol, and dry to obtain Co-zif67. Co-zif67 and sulfur powder are then calcined in a tube furnace in an argon atmosphere, and the sintering parameters are 600°C for 5 hours. 0.4wt% of the cobalt sulfide additive of the positive electrode active material is added to the initial positive electrode slurry, and ball milling beads are added to mix at high speed for 5 minutes, and then it is coated on the positive electrode current collector aluminum foil, and then dried at 120°C for 12 hours, rolled, and cut into pieces for use.

[0045] The above-mentioned electrode sheet was placed in the positive electrode shell, and the electrolyte was added in an amount of 4wt% of the mass of the positive electrode active material. A glass fiber separator (Whatman GF D), a gasket, and a negative electrode sodium sheet were added in sequence. The negative electrode shell was covered and the assembly was completed using a sealing machine.

[0046] Embodiment 2:

[0047] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0048] The positive electrode active material is Na 0.9 Ni 0.2 Fe 0.33 Mn 0.37 Al 0.05 Mg 0.05O2, the amount of cobalt sulfide additive is adjusted to 0.8wt% of the mass of the positive electrode active material, the amount of electrolyte added is 6wt% of the mass of the positive electrode active material, and the rest is the same as Example 1.

[0049] Embodiment 3:

[0050] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0051] The positive electrode active material is Na 0.67 Ni 0.1 Fe 0.1 Mn 0.7 Zr 0.05 Ti 0.05 O2, the novel sodium ion battery additive in the above-mentioned embodiment 1 is adjusted to zinc sulfide, and the addition amount of the electrolyte is 8wt% of the mass of the positive electrode active material, and the rest is the same as in embodiment 1.

[0052] Embodiment 4:

[0053] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0054] The positive electrode active material is Na 0.44 Ni 0.2 Fe 0.2 Mn 0.49 Zn 0.05 Li 0.05 Ca 0.01 O2, the novel sodium ion battery additive in the above-mentioned Example 1 is adjusted to molybdenum sulfide, and the addition amount of molybdenum sulfide is 0.5wt% of the positive electrode active material, the addition amount of the electrolyte is 10wt% of the mass of the positive electrode active material, and the rest is the same as Example 1.

[0055] Embodiment 5:

[0056] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0057] The positive electrode active material is Na 0.85 Ni 0.34 Fe 0.1 Mn 0.4 Mg 0.05 Nb 0.05 Y 0.05 Ru 0.01 O 1.99 F 0.01 The novel sodium ion battery additive in the above-mentioned Example 1 is adjusted to cobalt sulfide, and the addition amount of cobalt sulfide is 0.4wt% of the positive electrode active material, and the addition amount of electrolyte is 10wt% of the mass of the positive electrode active material. The rest is the same as Example 1.

[0058] Comparative Example 1:

[0059] Preparation of a semi-solid sodium ion battery and a sodium ion battery additive:

[0060] (1) The specific preparation method of the positive electrode sheet is:

[0061] NeNi 0.33 Fe 0.33 Mn 0.33 O2, conductive agent acetylene black, and binder PVDF are dissolved in NMP in a mass ratio of 90:5:5, and stirred evenly to obtain an initial positive electrode slurry; then it is coated on the positive electrode current collector aluminum foil, and then dried at 120°C for 12h, rolled, and cut into pieces for use.

[0062] The above-mentioned electrode sheet was placed in the positive electrode shell, and a glass fiber separator (Whatman GF D), electrolyte, gasket, and negative electrode sodium sheet were added in sequence, and the negative electrode shell was covered and assembled using a sealing machine.

[0063] The above embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0064] Table 1: Summary of performance of examples and comparative examples

[0065]

[0066] from Figure 1 It can be concluded from the XRD test diagram that the composite positive electrode sheet maintains the R-3m space group, which indicates that the introduction of additives does not affect the crystal configuration of the material and it still retains a pure O3 phase structure. Since the XRD test sample is a sheet, there will be impurity peaks of Al foil.

[0067] from Figure 2 According to the SEM test results, the NaNi Fe Mn elements on the electrode are evenly dispersed in the material, and the existence and uniform distribution of Co and S elements are proved.

[0068] from Figure 3 The XPS test results are shown in Figure 2. The charge calibration was performed using the carbon peak binding energy of 284.8 eV as the standard. The test results show that Co exists with a valence of +2 and +3, and S exists with a valence of -2. It also proves that the NaNi Fe Mn Co SO element exists on the prepared electrode.

[0069] from Figure 5,6,7 According to the electrochemical performance test results, the semi-solid-state battery has excellent cycle and rate performance. The 0.1C discharge capacity of Example 1 is 148mAh / g, the 5C discharge capacity is 98mAh / g, and the 100-cycle capacity retention rate is 91%. The 0.1C discharge capacity of Comparative Example 1 is 147mAh / g, the 5C discharge capacity is 75mAh / g, and the 100-cycle capacity retention rate is 71%.

[0070] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0071] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A semi-solid sodium ion battery, characterized in that: The general formula of the semi-solid sodium ion battery is: Na x (TM)O2, wherein TM is one or a combination of several transition metal ions, 0.44≤x≤1.0; the semi-solid sodium ion battery contains a sodium ion battery additive, and the sodium ion battery additive is a sulfide synthesized by a doped metal organic framework compound under a reducing atmosphere.

2. The semi-solid sodium ion battery according to claim 1, characterized in that: The preparation method comprises the following steps: S1, taking positive electrode slurry and sodium ion battery additives, ball-milling and mixing, and then evenly coating them on aluminum foil, and obtaining positive electrode sheets after drying; S2, adding electrolyte to the positive electrode sheet obtained in S1 as a positive electrode to assemble the semi-solid sodium ion battery.

3. The semi-solid sodium ion battery according to claim 1, characterized in that: S1 The positive electrode slurry includes a positive electrode active material, a conductive agent, a binder and a solvent; the positive electrode active material is at least one of layered transition metal oxides and modified compounds thereof, tunnel-type oxides and modified compounds thereof, etc., the binder is at least one of vinylidene fluoride, polytetrafluoroethylene, and fluorine-containing acrylic resin, the conductive agent includes at least one of carbon black, carbon nanotubes, acetylene black, graphene and carbon nanofibers, and the solvent is N-methylpyrrolidone.

4. The semi-solid sodium ion battery according to claim 3, characterized in that: The amount of the sodium ion battery additive added is 0.01 wt% to 0.1 wt% of the mass of the positive electrode active material.

5. The semi-solid sodium ion battery according to claim 3, characterized in that: The added mass ratio of the positive electrode active material, the conductive agent, the binder and the solvent is: (6-10): (1-10): (1-10): (10-30).

6. The semi-solid sodium ion battery according to claim 3, characterized in that: S2: The amount of the electrolyte added is 1wt% to 10wt% of the mass of the positive electrode active material.

7. The semi-solid sodium ion battery according to claim 1, characterized in that: S2 The electrolyte is an ester solvent, and the ester solvent includes one or more combinations of ethylene carbonate, propylene carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, methyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl butyrate, ethyl propionate and ethyl butyrate.

8. A sodium ion battery additive for a semi-solid sodium ion battery according to any one of claims 1 to 7, characterized in that: The invention relates to a metal organic framework compound obtained by carbonization infiltration, wherein the doped metal organic framework compound and sulfur powder are synthesized by low temperature sintering in a reducing atmosphere; the sodium ion battery additive is a combination of one or more of cobalt sulfide, molybdenum sulfide, zinc sulfide, selenium sulfide, nickel sulfide, manganese sulfide, tin sulfide and copper sulfide.

9. The sodium ion battery additive according to claim 8, characterized in that: The doped metal organic framework compound is a porous material assembled by metal ions or metal clusters and organic ligands through coordination bonds or other interaction forces, the metal ions are a combination of one or more transition metals, rare earth metals or alkaline earth metals, and the organic ligands are nitrogen-containing or oxygen-containing compounds, including a combination of one or more carboxylic acid compounds, pyridine compounds, and imidazole compounds.

10. The sodium ion battery additive according to claim 8, characterized in that: During the carbonization and sulfurization process, the ratio of the carbonized doped metal organic framework compound to the sulfur powder is 1:1-5, and the temperature of the low-temperature sintering is 500°C-700°C.

Citation Information

Cited By

  • Semi-solid sodium ion battery as well as preparation method and application thereof

    CN121484183A

  • Semi-solid sodium-ion battery and preparation method and application thereof

    CN121484183B